Report of the Irrigation and Power Team on Lakkavalli Project (Mysore State) - Committee on Plan Projects Planning Commission (Planning Commission, Government of India, 1957)
The Lakkavalli Project report for Mysore State outlines a comprehensive plan to enhance irrigation and power generation using the Bhadra River. With a dependable annual yield of 1,00,000 mcft, the project aims to irrigate approximately 2,34,000 acres and generate 40,400 KW of electricity. Key recommendations include phased construction for early benefits, strengthening technical staffing, establishing a centralized design office, and improving laboratory and monitoring facilities. The project emphasizes efficient financial management, hydropower optimization, and sustainable irrigation practices through soil surveys and revised water rates. Implementation of these measures is critical to maximize agricultural productivity and energy output, ensuring long-term benefits for the region.
Committee on Plan Projects Planning Commission New Delhi November 1957
Keywords: Lakkavalli Project; Mysore State; Irrigation; Power Generation; Bhadra River; Dam Construction; Phased Implementation; Technical Staff; Central Design Office; Hydropower; Water Management; Soil Surveys